Immunitet jurysdykcyjny państwa a prawa człowieka. Przegląd doktryny - Kotuła, Zuzanna (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2013)
Since the 1980s the number of actions for compensating damages caused by human rights violations brought before domestic courts has been increasing systematically. Therefore, some of the American and European courts formulated the postulate of non-recognition of jurisdictional immunity enjoyed by foreign States and, in consequence, of evaluation of the merits of the case in order to allow victims to pursue their claims against the alleged perpetrator in such cases. It has been noticed that, in some cases, a civil action is the only means of protection actually available to the victims of human rights abuses. This paper aims to present the contemporary trends in the development of the relationship between the State immunity and human rights law and to analyse critically the conceptions justifying the restriction of the State immunity restriction in the event of human rights abuse proposed so far by courts and doctrine, and to assess the opportunities and threats associated with the development of the institution of immunity in this direction. The realisation of the main objective of the paper is preceded by a detailed analysis of the sources of law of the State immunity and the determination of legal nature of this institution. Additionally, the ruling delivered in 2012 by the International Court of Justice in case Germany v. Italy is discussed, especially in view of its probable impact on further development of the State immunity in the analysed direction.
Keywords: prawo międzynarodowe